Comparison of Central Corneal Thickness Measurements by Contact and Non-contact Pachymetry Devices - Mayali, Huseyin (J Curr Glaucoma Pract, 2021)
AIM AND OBJECTIVE: To compare central corneal thickness (CCT) measurements obtained by handheld contact ultrasound pachymetry (HCUP) and non-contact pachymetry devices. MATERIALS AND METHODS: Ninety eyes of 90 patients (52 male and 38 female) were included in the study. Measurements from two non-contact devices, —specular microscopy (SM, Konan Medical, CA, USA) and Oculus Pentacam (Oculus Inc., Germany)—were compared against HCUP (Pachmate 2, DGH Technology, Inc, PA, USA). Ultrasound measurements were obtained 3 times by the same user and averaged. The differences were calculated by one-way ANOVA. Agreement between measurements were assessed by Bland–Altman plots and intraclass correlation coefficient tests. Coefficient of repeatability (%, CR) was defined as 1.96*standard deviations of the differences between pairs of measurements divided by the average of the means. RESULTS: The mean age was 34.31 ± 14.39 (14–74) years, and the mean intraocular pressure was 16.48 ± 2.63 mm Hg (12–21). Mean CCT measured by HCUP, SM, and Pentacam was 557.76 ± 36.76 μm, 550.29 ± 43.74 μm, and 541.41 ± 35.7 μm, respectively (p < 0.05). In the Bland–Altman plot, 95% limit of agreements were 19.5 and 14.18 μm among HCUP measurements, 34.55 μm between HCUP and Pentacam, 41.49 μm between SM and Pentacam, and 46.98 μm between HCUP and SM. CR values (%) were 3.49, 2.54, 6.28, 7.68, and 8.47, respectively. CONCLUSION: There were significant differences between the mean CCT values of the measurement devices. CLINICAL SIGNIFICANCE: Contact and non-contact devices may not interchangeable in the clinical assessment of CCT. HOW TO CITE THIS ARTICLE: Mayali H, Altinisik M, Diri I, et al. Comparison of Central Corneal Thickness Measurements by Contact and Non-contact Pachymetry Devices. J Curr Glaucoma Pract 2021;15(1):28–31.